Synthesis of Hydrophobic Coatings on Concrete Surface Using Organosilicone/TiO2 and Organosilicone/Carbon-Based Materials - Wellia, Diana Vanda; Yanni, Rahma; Hidayat, Benny (Jurnal Kimia Unand, 2025)
Surface coating methods provide protection for porous concrete surfaces against water diffusion, which can otherwise lead to structural damage and a reduction in concrete's service life. This study aims to assess the impact of varying quantities of biosynthesized TiO2 and coconut shell-derived carbon on concrete surface hydrophobicity and to compare their effectiveness in enhancing it. SEM analysis confirmed that the Organosilicone-based hydrophobic coating with 0,20 g of TiO2 and 0,20 g of carbon was uniformly distributed, covering micropores, and increasing concrete surface roughness. EDS analysis indicated a decrease in the Ca element peak and the absence of elements like Al, Fe, and K, validating the success of the concrete surface coating. FTIR analysis revealed the emergence of new absorption bands, such as 2963 cm-1 (aliphatic C-H bonds of Organosiliconee) and 477 cm-1 (Ti-O bonds), on the hydrophobic concrete surface. Contact angle measurements demonstrated hydrophobic behavior, with the B/Organosiliconee/TiO2 sample exhibiting an angle of up to 122,4º and the B/Organosiliconee/C sample up to 138,3º. Consequently, carbon derived from coconut shell waste emerges as a viable alternative for hydrophobic surface applications due to its superior hydrophobicity properties compared to TiO2.